Evaluation of water quality and potential scaling of corrosion in the water supply using water quality and stability indices: A case study of Juja water distribution network, Kenya. Issue 3 (March 2022) - Baloïtcha, Gbètingan Marien Patern; Mayabi, Alfred O.; Home, Patrick G.
Abstract: Drinking water quality describes the conditions for water to be accepted as suitable for human consumption. The water quality index is characterized by including, in the assessment process, water quality parameters such as physical, chemical and micro-biological. The availability of adequate management strategies to maintain good quality water has always been a challenge for water utilities. To proffer a solution to ths problem, a simple and effective tool that can be used to easily assess the quality of water is required. Water Quality Index (WQI) and Water Stability Index (WSI) are the most reliable tools for assessing water quality and aggressiveness. This study, therefore assessed the water quality, potential scaling and corrosion of the water supply in the Juja water distribution network by using WQI and WSI based on Langelier Saturation Index (LSI). Five sampling locations including the treatment plant outlet and consumption points were selected for physical, chemical and bacteriological water quality analysis and determination of WQI and WSI. It was found that 100 % of the collected water samples had Calcium concentrations within the World Health Organization (WHO) and Kenya Bureau of Standards (KEBS) acceptable ranges. Additionally, all the collected water samples had TDS concentrations within the WHO and KEBS acceptable ranges. However, water quality parameters such as Residual Chlorine, E. coli, Alkalinity, and Turbidity deviated from the WHO and KEBS standards. The pH values ranged from 6.29 to 8.06 and were generally within acceptable limits. The WSI ranged between – 3.04 to – 0.99, indicating that the water is generally corrosive and may pose a risk to water quality and shorten the lifespan of the network facilities. Generally, the water from the Treatment Plant was of good quality, while at consumption points, JKUAT Main Gate, JKUAT Campus, High Point, and Juja Stage had fair water quality based on the calculated WQI. Also, low concentrations of residual chlorine and E. coli slightly dropped the water quality at all the stations. Overall, the water quality deteriorated in the distribution network and was corrosive throughout the system right from the Treatment Plant based on the WQI and WSI. The water company needs to improve on the water quality chemically by adjusting the Calcium and Alkalinity concentration up to 40 mg/L CaCO3 as recommended for stable water and relook at management strategies of the network to provide better services to consumers. Abstract : Water quality, Water stability, Corrosive, Scaling, Water quality parameters.